Speaking mathematically : communication in mathematics classrooms - Pimm, David (Londen : Routedge, 1987)
David Pimm examines the school teaching of mathematics from the perspective of mathematics as a language.
Includes bibliography and index.
Keywords: Mathematics -- Study and teaching; Mathematical notation; Communication in education